Rosnę w teatrze – edukacja i wychowanie przez teatr jako alternatywa edukacyjna - Sanecka, Anna (Rocznik Pedagogiczny, 2022)
The analysis of theatre’s impact on children’s development usually takes into account four areas: social, emotional, cognitive and cultural. Group outings to theatre are usually an entertaining and pleasant way of spending time outside of school. The article shows, on the example of selected theatre performances dedicated to children aged 4–9 years, how theatre can become an alternative to school and what theatre can teach the youngest audience in the cognitive area. The content of the watched and experienced performances is likely to remain in the minds of the audience, while they quickly forget what they have learnt at school.